In vitro fertilization cycles stimulated with follitropin delta result in similar embryo development and quality when compared with cycles stimulated with follitropin alfa or follitropin beta - Olga Haakman, M.D.; Tina Liang, M.D.; Kristen Murray, B.Sc.; Angelos Vilos, M.D.; George Vilos, M.D.; Carlee Bates, Ph.D.; Andrew J. Watson, Ph.D.; Michael R. Miller, Ph.D.; Basim Abu-Rafea, M.D. (F&S Reports, 2021)
Objective: To study the impact of follitropin delta for ovarian stimulation on embryo development and quality compared with that of follitropin alfa or beta in in vitro fertilization/intracytoplasmic sperm injection (IVF/ICSI) cycles. Design: Retrospective cohort study Setting: University-affiliated, hospital-based fertility clinic Patient(s): A total of 403 IVF/ICSI cycles were conducted from September 1, 2018 to December 31, 2019. Cycles were grouped on the basis of stimulation with follitropin delta vs. follitropin alfa or beta. Intervention(s): None. Main Outcome Measure(s): Embryo parameters and clinical pregnancy and implantation rates. Result(s): Ovarian stimulation using follitropin delta resulted in no statistically significant difference in day 3 embryo quality between the control group and follitropin delta group (median 0.50 vs. 0.54 for good quality embryos and median 0.25 vs. 0.20 for intermediate quality embryos). Although on initial analysis there was a lower proportion of good quality blastocysts in the follitropin delta group than in the control group (0.11 vs. 0.22), this difference was no longer present when day 3 after fertilization vitrification and transfer cycles were excluded (0.26 vs. 0.33 follitropin delta vs. control). The clinical pregnancy rates and clinical implantation rates were similar in both groups in fresh transfer cycles. Conclusion(s): Stimulation with follitropin delta in IVF/ICSI cycles resulted in similar embryo development and pregnancy rates compared with those of stimulation with follitropin alfa or beta.